Comparative Study of the Two Elegies: Shawqi's Elegy upon “Hafiz Ibrahim” and Tennyson's “In Memoriam” - Rawan Haddad (My University, 2009)
This paper attempts to make a comparative study between two elegies: Tennyson's “InMemoriam” and Ahmad Shawqi's upon “Hafiz Ibrahim”. This study aims at showing how these two elegies focus on the same theme of lamenting a dear friend, yet there are many differences between the elegies in many respects, for instance, style, language and imagery. This study deals with the issue of friendship and faithfulness after death to show to what extent they are related to each other. This is due to the fact that friendship is the major element that provides relief in life.

This paper attempts to make a comparative study between two elegies: Tennyson's “InMemoriam” and Ahmad Shawqi's upon “Hafiz Ibrahim”. This study aims at showing how these two elegies focus on the same theme of lamenting a dear friend, yet there are many differences between the elegies in many respects, for instance, style, language and imagery. This study deals with the issue of friendship and faithfulness after death to show to what extent they are related to each other. This is due to the fact that friendship is the major element that provides relief in life.
Comparative Study of the Two Elegies: Shawqi's Elegy upon “Hafiz Ibrahim” and Tennyson's “In Memoriam”